Tea Plantation Workers and Their Working Circumstances: A Micro-Level Study - Kabir, M. Alamgir (Economic Journal of Nepal, 2011)
Low yield and high cost characterize the tea industry of Bangladesh, in addition to low crop yield. a large number of factors have contributed to the low productivity of tea workers. Even (after the enactment of different laws, tea workers’ right to safe. Secure and hygienic working conditions has not yet been ensured. This article triec to analyze the causes of low productivity of tea workers based on data drawn from in-depth interviews and discussions with the associated authorities and tea workers at the grass root level. A total of 120 workers (70 females and 50 males) were interviewed through a structured questionnaire. Key words: Labour problem; Tea plantation; Bangadesh Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.3, July-September, 2007 Page: 184-196 Uploaded date: 22 July, 2011